1007 Sociodemographic, Lifestyle and Dietary Correlates of Actigraphy-Measured Irregular Sleep Schedules in the Multi-Ethnic Study of Atherosclerosis. (27th May 2020) - Huang, T; Chung, J; Reid, M; Johnson, D A; Billings, M E; Klerman, E B; Redline, S
Abstract: Introduction: Increasing evidence links daily variability in sleep schedules to increased cardiometabolic risk. Little is known, however, regarding sociodemographic and behavioral correlates of irregular sleep schedules that may help identify causes or consequences of irregular sleep. Methods: Among 1, 946 participants from the Multi-Ethnic Study of Atherosclerosis, we examined the cross-sectional associations of irregular sleep schedules with sociodemographic, lifestyle, dietary factors, and actigraphy-based indices of rest-wake rhythms using multiple linear regression with adjustment for age, sex, race/ethnicity, education, income, marital status and work schedules. Sleep regularity was assessed using standard deviations (SD) in actigraphy-measured sleep duration and sleep onset timing across 7 days. Results: Compared to Whites, the 7-day sleep duration SD (95% CI) was 17.4min (12.6, 22.2) higher in African-Americans, 10.4min (4.8, 16.0) higher in Hispanics and 7.9min (1.3, 14.4) higher in Chinese. Shift versus regular work was associated with 11.4min (5.1, 17.7) higher sleep duration SD. Irregular sleep duration was associated with lower income (p=0.006), higher depressive symptoms (p<0.0001), higher BMI (p=0.004) and current smoking (p=0.06). Higher sleep duration variability was associated with lower Alternative Healthy Eating Index (p=0.01), mainly due to suboptimal intakes of fruits, whole grains and nuts/legumes. No associations were observed for age, sex, education, marital status or number of meals per day. While sleep duration variability was not associated with self-reported physical activity level or actigraphy-measured 7-day mean activity count, sleep duration SD was inversely associated with relative amplitude (difference between the most versus the least active period; p<0.0001) and inter-daily stability (synchronization between rest-activity patterns and environmental zeitgebers; p<0.0001) of 24-h rest-activity patterns. Similar results were observed for sleep onset timing SD. Conclusion: Substantial differences by sociodemographic factors exist regarding the consistency of day-to-day sleep schedules. Irregular sleep schedules are associated with overall circadian disruption across the day and some unhealthy lifestyle behaviors. Future studies are needed to understand temporal relationships of the observed associations. Support: NIH grants K01HL143034, R35HL135818